Hydrology–Soil–Vegetation Element Interactions in the Largest Single-Port Artesian Irrigation Area of Asia - Ziniu Wang; Limin Duan; Yahui Han; Jianxun Ji; Qiwei Shi; Rongjiang Yao; Yanyun Luo; Tingxi Liu (Land)
Climate change and anthropogenic activities have increased the complexity of hydrology–soil–vegetation interactions in arid-region irrigation areas. Therefore, studies on the spatiotemporal characteristics of these interactions can greatly benefit the sustainable development of arid areas. This study developed a spatially granular dataset of the key hydrology, soil, and vegetation elements for the Hetao Irrigation District (HID) for 2000–2020, recognized as the largest single-port artesian irrigation area in Asia, and explored the interactions between these elements by means of a geodetector, the analytic hierarchy process, and the Pearson correlation coefficient. The key results indicated the following: (1) a declining trend of 0.1–0.15 in the comprehensive influence of hydrology–soil–vegetation interactions; increasing significance of hydrologically driven soil and vegetation evolution, with feedback between soil and vegetation; (2) the maximization of the interactions between soil moisture and precipitation and groundwater, with evapotranspiration as the dominant factor regulating hydrology–vegetation interactions; (3) the interactions between hydrology, soil, and vegetation showing nonlinear synergism; (4) and the spatial distributions of the hydrology–soil–vegetation interactions showing significant band-like patterns with weak coupling between the elements.